Antidiarrheal Activity of Methanolic Extract of Leaves of Gymnosporia Emerginata - A. Suvarchala Kiranmai, Hemamalini. K, P. Sumalatha, G Shashi Priya and Uma Vasireddy (Journal of Applied Pharmaceutical Science, 2013)
The methanolic leaf extract of Gymnosporia emerginata showed significant antidiarrheal activity on castor oil induced diarrheal model in rats. These results obtained revealed that the leaf extract possess pharmacological activity against diarrhea and may possibly explain the use of the plants in traditional medicine.
Keywords: Atropine, Antidiarrheal, Gymnosporia emerginata.